An evaluation of the implementation of the continuing learning delivery system of Concordia Development Center, Manila, 1983-1986 - Alcantara, Aranda N. (Animo Repository, 1986)
The study evaluates the continuing learning delivery system program implementation of Concordia Development Center from 1983-1986. This study used the process evaluation model of evaluation by Stufflebeam (1971). The descriptive-normative survey method was utilized since the primordial concern of the study was the description of the CLDS program implementation. The survey was normative because it sought to obtain facts or data concerning the recent status of the program implementation and its sources of failure, if any. The study took as subjects the administrators and CLDS staff, CLDS teachers, the CLDS graduates and past enrollees from 1983-1985 and the current enrollees of the CLDS program, 1985-1986. There were 3 administrators, 22 teachers, 2 CLDS staff, 40 CLDS past enrollees and 47 current enrollees as the aggregate population size which total 114 in all. The total population was included in the study. The conclusions derived were: 1. The intellectual development of persons was perceived to be one of the most important aspects of growth that will lead to self-reliance and contributing members of society. The CLDS as a new educational thrust maybe viewed as a relevant activity for the intellectual upliftment of those being served specifically the school drop-outs as well as those who have not gone to formal school. 2. The CDC-CLDS is an alternative schooling catered to the needs of the country's out-of-school youth and adults in this time of economic difficulty to raise their educational level without going through the formal classroom system. The CLDS program is an avenue in accomplishing the mission of the Church and of the school in promoting the dignity of persons particularly the most deprived in the larger community.3. The CDC-CLDS has achieved its objectives of: a. Providing education to out-of-school youths and adults so they can participate actively in the economic upliftment of the country. b. Developing the proper attitude of the learners toward studies so as to realize and actualize their pote